2018
DOI: 10.1038/s41375-018-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 fusion kinase regulation of MYC expression drives development of stem cell leukemia/lymphoma syndrome

Abstract: Oncogenic transformation of hematopoietic stem cells by chimeric fusion kinases causing constitutive activation of FGFR1 leads to a stem cell leukemia/lymphoma (SCLL) syndrome, accompanied by widespread dysregulation of gene activity. We now show that FGFR1 activation is associated with upregulation of MYC and pharmacological suppression of FGFR1 activation leads to downregulation of MYC and suppression of MYC target genes. Luciferase reporter assays demonstrate FGFR1 can directly regulate MYC expression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Activation of FGFR1 in SCLL implies a role for tyrosine phosphorylation of target proteins that is associated with leukemogenesis and indeed known targets of FGFR1 such as PLCG2 and SRC are activated . However, we have recently reported that the chimeric kinases seen in SCLL can be cleaved by granzyme B, to generate a truncated form of FGFR1, which is not phospho‐activated and which specifically translocates to the nucleus, where it is presumed to activate gene expression that contributes to the promotion of SCLL . We now demonstrate the relative contribution of the BCR STK domain in the development of SCLL, using transduction and transplantation experiments in syngeneic mice using mutant chimeric kinases .…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Activation of FGFR1 in SCLL implies a role for tyrosine phosphorylation of target proteins that is associated with leukemogenesis and indeed known targets of FGFR1 such as PLCG2 and SRC are activated . However, we have recently reported that the chimeric kinases seen in SCLL can be cleaved by granzyme B, to generate a truncated form of FGFR1, which is not phospho‐activated and which specifically translocates to the nucleus, where it is presumed to activate gene expression that contributes to the promotion of SCLL . We now demonstrate the relative contribution of the BCR STK domain in the development of SCLL, using transduction and transplantation experiments in syngeneic mice using mutant chimeric kinases .…”
Section: Introductionmentioning
confidence: 66%
“…Resistance to FGFR1 inhibitors, however, in model systems, occurs through mutation of the FGFR1 kinase and deletion of PTEN requiring alternative strategies . In various preclinical studies, we have shown the potential benefit of targeting SRC, PI3K, Notch, MYC, BCL2 and now SHP2 as a potential therapeutic strategy, either alone or more likely in combination with other critical pathways promoting SCLL. While SCLL is a relatively rare disease, our recent demonstration that up to 20% of de novo AML also overexpress FGFR1 and that FGFR1 inhibitors can suppress their growth in human xenografts in immunocompromised mice, suggesting that developing targeting strategies against the consequences of FGFR1 activation in AML may have a more widespread application .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, the recent clinical trials and findings showed limited efficacy of FGFR-targeted therapy in multiple malignant tumors, suggesting that combination therapy may be essential to improve the EGFR1-amplified patient outcomes [35][36][37]. Golfmann et al postulated synergistic treatment effects in FGFR1/VEGFR1-positive breast cancer patients by dual targeting of FGFR and VEGFR [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although TKI therapies have been used to traditionally treat certain hematopoietic cancers, their use has often resulted in drug resistance. Recently it was discovered that FGFR1 fusion kinases are associated with the upregulation of MYC, which drives SCLL (35). Targeting the MYC complex in addition to chemotherapy, and the approaches described here may also be therapeutically beneficial for patients with SCLL.…”
Section: Novel Therapeutic Targets For Scll Induced By Bcr-fgfr1mentioning
confidence: 92%